Work-life Balance terhadap Turnover Intention melalui Kompensasi sebagai Variabel Intervening - Azhar, Muhammad Hadiputra; Khan, Ryan Basith Fasih (Jurnal E-Bis, 2024)
This study aims to realize the effect of work-life balance on turnover intention and compensation as a mediating variable in Generation Z workers in Malang City. The method used in this research is a quantitative approach with descriptive analysis. The sample uses non probability sampling, namely saturated samples or census. The number of samples in this research are generation Z workers in Malang City as many as 100 workers. In the data collection process, the method used is a questionnaire. The data was tested using SmartPLS. The results of this research found that work-life balance has no effect on turnover intention, compensation has a positive effect on turnover intention, work-life balance has a positive effect on compensation, and compensation has no effect in mediating work-life balance turnover intention in Generation Z workers in Malang City. Keywords: Work-life Balance, Turnover Intention, Compensation, Z Generation